Germinal Mosaicism in a Family With BO Syndrome. (May 2015) - Miyagawa, Maiko; Nishio, Shin-ya; Hattori, Mitsuru; Takumi, Yutaka; Usami, Shin-ichi
Objectives: To clarify the existence of germinal mosaicism, we performed a genetic analysis of 2 siblings identified with an EYA1 mutation associated with branchiooto (BO) syndrome but who were born from normal parents. Methods: Detailed data from the 2 affected siblings were collected for clinical diagnosis, with haplotype analysis also performed to prove germinal mosaicism. Results: The 2 sisters showed characteristic clinical features of BO syndrome (middle and inner ear anomalies, microtia, and auditory canal stenosis/atresia). Haplotype analysis confirmed the genetic relationship between the affected sisters and their parents. The younger sister with auditory canal atresia received a bone-anchored hearing aid (Baha), a transcutaneous bone conduction hearing device, resulting in a good hearing outcome. Conclusions: Based on the results of haplotype analysis, we proved that the BO syndrome in these cases was caused by germinal mosaicism of the EYA1 gene in either the mother or father. We also demonstrated that the bone-conduction hearing implant is a good option for BO patients with complex outer, middle, and inner ear anomalies.